Brazil’s fight against narcotraffic in the border with Colombia : an approach to the restrains of non-traditional threats over foreign policy - Calderón, Emilse (2014)
Fil: Fil: Calderón, Emilse. Universidad Nacional de Rosario. Facultad de Ciencia Política y Relaciones Internacionales; Argentina.